2011
DOI: 10.1016/j.jvolgeores.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Scale-dependent location of hydrothermal vents: Stress field models and infrared field observations on the Fossa Cone, Vulcano Island, Italy

Abstract: Hydrothermal venting occurs on numerous volcanoes of various age, setting, topographic and structural expression. Vent locations are commonly found not within volcanic craters only, but predominantly at the crater margins and topographic highs. A case example is Vulcano Island, Italy, where the control on such vent locations along crater margins remained poorly understood, however. This paper describes numerical models combined with field observations and infrared imaging to explore the mechanisms that control… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…4a). As mentioned in the BIntroduction,p athways of the ascending fluids including CO 2 are controlled by topography, lithology, and/or volcano-tectonic structures (Schöpa et al 2011;Peltier et al 2012;Pantaleo and Walter 2014;Hutchison et al 2015). Here, we evaluate possibilities of these factors.…”
Section: Pathway Of Diffuse Comentioning
confidence: 95%
See 3 more Smart Citations
“…4a). As mentioned in the BIntroduction,p athways of the ascending fluids including CO 2 are controlled by topography, lithology, and/or volcano-tectonic structures (Schöpa et al 2011;Peltier et al 2012;Pantaleo and Walter 2014;Hutchison et al 2015). Here, we evaluate possibilities of these factors.…”
Section: Pathway Of Diffuse Comentioning
confidence: 95%
“…Recently, Hutchison et al (2015) presented evidence that, at Aluto volcanic complex, Main Ethiopian Rift, the fluid pathways are controlled not only by pre-and post-caldera structures at large scale but also by topography and surface lithology at small scale using soil CO 2 flux measurements and geomorphological analyses. This idea is based on recent thermal infrared imagery studies focusing on the fluid ascent in volcanoes (Schöpa et al 2011;Peltier et al 2012;Pantaleo and Walter 2014). Schöpa et al (2011) showed that, at Vulcano Island, positions of the fumaroles around the crater rims are controlled by topography at the large scale and by lithology and structures at small scale.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, in the last 30 years, CO 2 spatial distribution has been used worldwide to identify hidden tectonic structures, since faults/fractures act as preferential pathways (high permeability zones) for the escape of gases from the deep crust or mantle to the surface (Giammanco et al, 1999(Giammanco et al, , 2006Baubron et al, 2002;Hutchison et al, 2015;Liuzzo et al, 2015). Based on the release of soil gases in confined areas, Chiodini et al (2001) named the anomalous CO 2 degassing areas, where hydrothermal/volcanic CO 2 is released, as diffuse degassing structures (DDS), whose shape depends on morphological, geological, and structural factors, such as the topography, existence of lithological heterogeneities, and presence of faults/fractures (Schöpa et al, 2011;Peltier et al, 2012;Pantaleo and Walter, 2014).…”
mentioning
confidence: 99%